2014
DOI: 10.1002/ijc.28834
|View full text |Cite
|
Sign up to set email alerts
|

HPV self-sampling as primary screening test in sub-Saharan Africa: Implication for a triaging strategy

Abstract: Our objective was (i) to assess if a self-collected test for human papillomavirus (HPV) may serve as a primary cervical cancer screening method in a low-resource setting, (ii) to evaluate its implication in a screen and treat approach and (iii) to identify the most eligible age group in a screening program. Women were recruited through a cervical cancer screening campaign conducted in Cameroon. Written and oral instructions were given to participants by a health-care professional to carry out an unsupervised s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 24 publications
(55 reference statements)
1
42
0
Order By: Relevance
“…9 HPV infection is a very common condition in young women with prevalence over 25% in those aged younger than 30 years in Cameroon. 14 Studies carried out in other African countries found a PPV for HPV testing to be lower than 30%. [15][16][17] These findings indicate that a triage test following a positive HPV result is necessary to limit the rate of false positive and consequently the harms of overtreatment.…”
mentioning
confidence: 98%
“…9 HPV infection is a very common condition in young women with prevalence over 25% in those aged younger than 30 years in Cameroon. 14 Studies carried out in other African countries found a PPV for HPV testing to be lower than 30%. [15][16][17] These findings indicate that a triage test following a positive HPV result is necessary to limit the rate of false positive and consequently the harms of overtreatment.…”
mentioning
confidence: 98%
“…HPV genotypes were identified from differences in the relatively conserved L1, E6 and E7 open reading frame, when HPV gene sequences had a less-than 90 % homology with L1, E6 and E7 open reading frame, it was defined as a new HPV genotype [19]. Because of the complicated structure of HPV trait, each HPV genotype can only aim at the structure specificity to develop the corresponding vaccine research [21][22][23]. There are at present no effective treatments for human papilloma virus, so only through large-scale physical examination acquire a very large number of first-hand data about the epidemic characteristics of HPV in China [21,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Because of the complicated structure of HPV trait, each HPV genotype can only aim at the structure specificity to develop the corresponding vaccine research [21][22][23]. There are at present no effective treatments for human papilloma virus, so only through large-scale physical examination acquire a very large number of first-hand data about the epidemic characteristics of HPV in China [21,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…However, the effectiveness of screening by self-sampling is determined in part by the performance of the HPV PCR test when applied to self-samples 23 . To bridge the prevention gap in low-/middle- income settings, approaches such as hrHPV self-testing are viable and enable invitation of communities who test positive to attend further triaging 24, 25 . Visual inspection of the cervix with acetic acid (VIA) or Lugol’s iodine (VILI) is a particularly simple and low-cost screening tool that enables trained healthcare workers to detect abnormalities with a speculum examination.…”
Section: Advances In Screeningmentioning
confidence: 99%